Screening the allelopathic activity of 14 medicinal plants from Northern Thailand - Prapaipit Suwitchayanon (2018)
Fourteen medicinal plants from northern Thailand, which dominate and form large colonies, were dried, powdered, and evaluated for growth inhibitory activity using a modified sandwich method. All the plants showed inhibitory activities on the growth of lettuce seedlings: Cymbopogon nardus had the strongest activity, completely inhibiting the growth of the lettuce hypocotyls and radicles; Piper retrofractum completely inhibited the hypocotyl growth and 93.5% of the radicle growth; and the remaining plants inhibited hypocotyl and radicle growth by 30.9 57.4% and 44.1 75.3%, respectively. Inhibitory active compounds may have been released from the plants into the sandwich method medium and inhibited the growth of the lettuce seedlings. The present results suggest that C. nardus and P. retrofractum are possible candidates for developing alternative natural herbicides in sustainable agriculture because of their strong inhibitory activity.